FAKTOR-FAKTOR YANG MEMPENGARUHI PUTUS BEROBAT PADA PENGOBATAN TB PARU DENGAN STRATEGI DOTS (DIRECTLY OBSERVED TREATMENT SHORT COURSE) DI PUSKESMAS BANDAR KHALIPAH TAHUN 2022 - MURNI ARITONANG (LP2MTBM MAKARIOZ, 2022)
Pulmonary TB is the third leading cause of death after cardiovascular and respiratory diseases. Since 1995, the TB eradication program has been implemented using the DOTS (Directly Observed Treatment Shortcourse) strategy in which WHO targets a cure rate of at least 85% of pulmonary TB patients detected at the Bandar Khalipah Health Center. The DOTS strategy has been implemented at the Bandar Khalipah Health Center, but it has not yet reached the target of a cure rate below 85%. The purpose of this study was to determine the factors associated with dropout in pulmonary TB patients in terms of the DOTS strategy. This type of research is an analytic survey with a cross sectional approach and the results of this study are presented in a frequency distribution table, where the statistical test used is chi square. The results of this study indicated that there was a significant relationship between PMO and dropout with a p value = 0.013, and recording and reporting with a p value = 0.001 was tested using the chi square test.